Experimental Study on Vibration-Assisted Magnetic Abrasive Finishing for Internal Surface of Aluminum Tubes - Givi, M.; Tehrani, A. F.; Mohammadi, A.; Vahdati, M. (Journal of Advanced Manufacturing Technology (JAMT), 2017)
In this research, a new apparatus is designed and set to polish the internal surface of aluminum tube in the presence of axial vibration (AV) for the poles. Several parameters influence the quality of polished surface during magnetic abrasive finishing. The effect of such parameters has been the subject of researches to achieve the best finished surface with desired characteristics. This paper has a statistical approach to investigate the effects of four parameters, i.e., mesh size of the abrasives, the weight of the abrasive powders, the number of cycles and especially vibration frequency of the poles on surface roughness and material removal weight in finishing process. Design of experiments (DOE) methods and analysis of variance are applied to determine the significant factors. Microscopic view of the working surface is also presented for better understanding the parameters effect on the finished surface.